2015
DOI: 10.14419/ijaa.v3i1.4334
|View full text |Cite
|
Sign up to set email alerts
|

Higher order resonance stability of triangular libration points for radiating primaries in ER3BP

Abstract: The main aim of this paper is to study the existence of resonance and stability of the triangular equilibrium points in the framework of ER3BP when both the attracting bodies are sources of radiation atin both circular and elliptical cases .A practical application of this model could be seen in the case of binary systems ( Achird, Luyten, α Cen-AB, Kruger 60, Xi Bootis). The study is carried out both analytically and numerically by considering various values of radiation pressures and around binary systems .In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Recently [32] studied nonlinear stability of the triangular points considering both the primaries as radiating in ER3BP in non-resonance case .It was found that the except for some values of radiation pressure the triangular points are stable. The resonance condition was also studied by [33] considering only radiating primaries and observed that the motion is stable for third order resonance but unstable for fourth order resonance.…”
Section: Discussionmentioning
confidence: 99%
“…Recently [32] studied nonlinear stability of the triangular points considering both the primaries as radiating in ER3BP in non-resonance case .It was found that the except for some values of radiation pressure the triangular points are stable. The resonance condition was also studied by [33] considering only radiating primaries and observed that the motion is stable for third order resonance but unstable for fourth order resonance.…”
Section: Discussionmentioning
confidence: 99%
“…The stability of the triangular equilibrium points in CR3BP is investigated when both primaries are radiating and oblate, under the nonresonance case using KAM theory. Recently Narayan and Singh [5] studied nonlinear stability considering both primaries as radiating in ER3BP and found that the binary systems are stable. It has been observed that in general the stability character remains the same even if oblateness factor is considered apart from radiation factor in circular cases.…”
Section: Discussionmentioning
confidence: 99%
“…The nonlinear stability of the triangular Lagrangian points, considering the bigger primary as oblate spheroid in circular case, was examined by Markellos et al [4]. Recently Narayan and Singh [5] studied the nonlinear stability of higher order for both radiating primaries and found that binary systems are stable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation